Domestic courts and the interpretation of international law : methods and reasoning based on the Swiss example - Ammann, Odile (Developments in international law, 2020)
"This book's epigraph, written by Manley O. Hudson, dates back to 1947. Today, more than seven decades later, Hudson's optimistic remarks about Switzerland's expected compliance with international law leave us wondering how the practice of the Swiss authorities has evolved. Has Switzerland indeed been 'chart[ing] her course with meticulous regard for her obligations under international law"--